Using the Step it UP! Game to increase physical activity during physical‐education classes. Issue 2 (14th August 2019) - Normand, Matthew P.; Burji, Carla
Abstract : The Step it UP! Game is an interdependent group reinforcement contingency based on the Good Behavior Game. We evaluated the effects of the Step it UP! Game on the number of steps taken by 3rd‐grade students during physical‐education (PE) classes at a local public elementary school. We divided the class into 2 teams and awarded a "Step it UP! Champ" badge to the members of the team with the highest mean step totals at the end of each game. We used a reversal design to compare the mean number of steps taken while playing the game and during regular PE classes. Overall, participants took more steps while playing the game than they did during class periods without the game. When given the opportunity to choose playing the Step it UP! Game or having regular PE class during a follow‐up session, 16 of 18 participants voted to play the game.